Synopsis of orthopaedic trauma management - Mullis, Brian H.; Gaski, Greg E. (Thieme, 2020)
"Orthopaedic trauma spans the full spectrum of injury, from simple fractures to life-threatening accidents with multiple broken bones. As such, these incidents are a common reason patients visit emergency departments and receive treatment from orthopaedic surgeons. Synopsis of Orthopaedic Trauma Management by nationally recognized experts Brian Mullis, Greg Gaski, and esteemed contributors fills a gap in the literature by providing a concise yet comprehensive reference for evaluating these conditions and initiating immediate treatment. The text provides a well-rounded perspective on the surgical and nonsurgical management of trauma in adult and pediatric patients. The opening section lays a solid foundation, with chapters covering physiology, open and closed fracture management, imaging, biomechanics, complications, and other core topics. Subsequent chapters address a full compendium of orthopaedic procedures to treat traumatic conditions of the upper and lower extremities, pelvis, and spine. Key Features Bulleted format provides quick and authoritative navigation of essential information needed for effective treatment A wealth of high-quality illustrations, radiographic images, and tables supplement concise text Uniformly organized chapters include up-to-date, clinically relevant statistics and suggestions for further reading Videos by renowned experts enhance understanding of specific fractures and orthopaedic surgery approaches This is a must-have resource for providers who treat orthopaedic trauma patients, including general and orthopaedic surgeons, residents, ER physicians, nurse practitioners, physician assistants, nurses, medical students, and others on call. It also provides a robust review for orthopaedic residents prepping for the boards"--